2020
DOI: 10.1088/1757-899x/765/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a single-side flat synchronous linear motor model

Abstract: In recent decades, the demand for a linear motor has increased in various applications, due to its ability to develop a linear motion directly. One of the significant problems facing the operation of the linear motor is the presence of force ripple caused by the irregular magnetic field of the permanent magnets. Accordingly, a developed single-side permanent magnet synchronous flat linear motor (PMSLM) model has been designed based on minimizing its force ripple produced. A Maxwell ANSYS simulation is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The studies [5] The progress of research should be described with references, so that the explanation may be accepted scientifically [2], [4]. As seen below and cited in the manuscript [5], [8]- [13], Figures 1-2…”
Section: Hydroelectric System Simulator For Telescopic Elevatormentioning
confidence: 99%
“…The studies [5] The progress of research should be described with references, so that the explanation may be accepted scientifically [2], [4]. As seen below and cited in the manuscript [5], [8]- [13], Figures 1-2…”
Section: Hydroelectric System Simulator For Telescopic Elevatormentioning
confidence: 99%
“…The analysis of motor structure parameters was performed using the commercial finite element package based on Maxwell ANSYS depending on Maxwell equations that ignored end windings due to using 2D model [8]. The solution was divided into two stages, load and no-load transient magnetic solution, to analyze and optimize the magnetic and force characteristics of the linear motors LM for solving the nonlinear transient magnetic problem.…”
Section: Linear Synchronous Motormentioning
confidence: 99%
“…Raghda'a, Farag and Jamal [8], A Maxwell ANSYS simulation was performed to study and enhance the dynamic characteristics and performance of the model. The results of the improved model design showed that the maximum value of the force ripple is reduced by about 81.13% as compared with the primary model at a smaller ripple coefficient of 0.22%.…”
Section: Introductionmentioning
confidence: 99%